2019
DOI: 10.1002/anie.201906825
|View full text |Cite
|
Sign up to set email alerts
|

Defluorosilylation of Industrially Relevant Fluoroolefins Using Nucleophilic Silicon Reagents

Abstract: An umber of new magnesium and lithium silyl reagents were prepared and shown to be outstanding nucleophiles in reactions with industrially relevant fluoroolefins. These reactions result in an et transformation of either sp 2 or sp 3 CÀFbonds into CÀSi bonds by two modes of nucleophilic attack( S N VorS N 2'). The methods are mild, proceeding with high chemo-and regioselectivity.M echanistic pathways are described that lead to new substitution patterns from HFO-1234yf,H FO-1234ze,a nd HFO-1336mzz, previously in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 36 publications
0
35
0
Order By: Relevance
“…[4b, 7] Alkali and alkaline earth metal silanides catalyze such reactions as hydrofunctionalizationo fo lefins and pyridine, [8] and are also activei nt he defluorination of organofluorides. [9] Recently,w es howedt hat the molecular complex [(Me 6 TREN)KSiPh 3 ]r eacts with H 2 to give as oluble form of [a-KSiH 3 ] 1 . [10] Herein, we report the synthesis of the full range of alkali metal triphenylsilanidess tabilized by the macrocyclic ligandM e 4 TACD (1,4,7,10-tetramethyl-1,4,7,10- the volatile by-products (Me 3 Si) 2 CH 2 or tBuOSiMe 3 were readily removed under reduced pressure.A lternatively,l igand exchange from isolatedT HF adducts [(thf) x MSiPh 3 ]( M= Li, K-Cs) with L also gave complexes 1 and 3-5.…”
mentioning
confidence: 99%
“…[4b, 7] Alkali and alkaline earth metal silanides catalyze such reactions as hydrofunctionalizationo fo lefins and pyridine, [8] and are also activei nt he defluorination of organofluorides. [9] Recently,w es howedt hat the molecular complex [(Me 6 TREN)KSiPh 3 ]r eacts with H 2 to give as oluble form of [a-KSiH 3 ] 1 . [10] Herein, we report the synthesis of the full range of alkali metal triphenylsilanidess tabilized by the macrocyclic ligandM e 4 TACD (1,4,7,10-tetramethyl-1,4,7,10- the volatile by-products (Me 3 Si) 2 CH 2 or tBuOSiMe 3 were readily removed under reduced pressure.A lternatively,l igand exchange from isolatedT HF adducts [(thf) x MSiPh 3 ]( M= Li, K-Cs) with L also gave complexes 1 and 3-5.…”
mentioning
confidence: 99%
“…40 The same group recently reported on a double defluorosilylation of a CF 3 moiety via an initial S N 2′ reaction with magnesium or lithium silyl derivatives leading to (PhMe 2 -Si)CH 2 CF=CF(SiMe 2 Ph). 41 In addition, Crimmin and coworkers also developed a defluoroborylation of a sp 3 C-F bond with a B-Li-based reagent followed by C-C coupling reactions to form CH 2 =CFCF 2 C(OH)R 1 R 2 (R 1 , R 2 = H, alkyl or aryl groups) in the presence of a ketone or aldehyde. 42 It is interesting to compare the chemistry of 2,3,3,3tetrafluoropropene (HFO-1234yf) with its isomer (E)-1,3,3,3tetrafluoropropene (HFO-1234ze).…”
Section: Account Synlettmentioning
confidence: 99%
“…40 Furthermore, in contrast to the studies with rhodium, magnesium or lithium silyl derivatives resulted in the formation of the corresponding silylated trifluoromethylethene, CF 3 CH=CH(SiMe 2 Ph), by activation of the C(sp 2 )-F bond. 41 When using a lithium boryl derivative, Crimmin et al recently reported on a double C-F bond activation followed by a C-C coupling to form CH 2 =CHCF 2 C(OH)(naphthyl) by addition to naphthaldehyde. 42 Catalytically, both tetrafluoropropenes described in this account show comparable reaction pathways.…”
Section: Account Synlettmentioning
confidence: 99%
“…We hypothesised that the defluoroalkylation of HFO-1234yf couldb ea chieved by as tepwise S N 2'/S E 2' reaction sequence mediated by main group reagents. [27,28] The key challenge being the identification of reagentt hat allows control of the selectivity of both steps without loss of fidelity over which site (a or g)o ft he allylic system reacts( Figure 1).…”
mentioning
confidence: 99%
“…The minor isomer is proposed to derive from ad irect S N Vm echanism. [27] Attempts to crystallise 2a-c provedu nsuccessful. Isolation was likely compromised by the slow decomposition of these reagents in hydrocarbon solutions.…”
mentioning
confidence: 99%